Lactose intolerance in patients with chronic functional diarrhoea: the role of small intestinal bacterial overgrowth - ZHAO, J.; FOX, M.; CONG, Y.; CHU, H.; SHANG, Y.; FRIED, M.; DAI, N. (Alimentary pharmacology & therapeutics, 2010)
Aliment Pharmacol Ther 31, 892–900 Summary Background  Many studies report a high prevalence of lactose intolerance in patients with functional, gastrointestinal disease. Aim  To evaluate the role of small intestinal bacterial overgrowth (SIBO) in condition of lactose intolerance and the mechanism by which SIBO may impact lactose tolerance in affected patients. Methods  Consecutive out‐patients with chronic functional diarrhoea (CFD) and healthy controls underwent a validated 20 g lactose hydrogen breath test (HBT). Patients completed also a 10 g lactulose HBT with concurrent assessment of small bowel transit by scintigraphy. Results  Lactose malabsorption was present in 27/31 (87%) patients with CFD and 29/32 (91%) healthy controls (P = 0.708). From the patient group 14/27 (52%) had lactose intolerance and 13/27 (48%) experienced no symptoms (lactose malabsorption controls). Only 5 (17%) healthy controls reported symptoms (P < 0.01). The oro‐caecal transit time was similar between patient groups with or without symptoms (P = 0.969). SIBO was present in 11 (41%) subjects and was more prevalent in lactose intolerance than in lactose malabsorption [9/14 (64%) vs. 2/13 (15%), P = 0.018]. Symptom severity was similar in lactose intolerance patients with and without SIBO (P = 0.344). Conclusions  Small intestinal bacterial overgrowth increases the likelihood of lactose intolerance in patients with CFD as a direct result of lactose fermentation in the small intestine, independent of oro‐caecal transit time and visceral sensitivity.